The Corporate Mechanism Relationship with Stress Levels in Final State Students of Nursing - Nur Fauziyah, Dini; Apipudin, Aap; Nurapandi, Adi; Rahmawati, Elis (LPPM STIKes Muhammadiyah Ciamis, 2024)
Purpose: The most difficult tasks for final year students is thesis. this study aims to determine the relationships between coping mechanisms and stressed levels in Nursing STIKes Muhammadiyah Ciamis undergraduate students. Methods: The design in this study was cross sectional. Sampling was done by using total sampling. The sample in this study amounted to 83 people. Results: The results of statistical tests showed that there was a relationship between stressed levels and coping mechanisms in final year undergraduate students of Nursing STIKes Muhammadiyah Ciamis 2-8 July 2023 (p=0.022). This study provides an overview for undergraduate nursing students to b able to understand and improve emotional intelligence , so that they are able to motivated themselves and can withstand stress.